Effect of solid loading on properties of Cr2O3 refractories by aqueous gelcasting. (May 2015) - Ding, C. H.; Zhang, C.; Di, L. Z.; Zhai, T.; Lu, L. X.; Yang, D. A.
Abstract : Dense chromic oxide refractories were prepared by aqueous gelcasting process. Effect of solid loading on rheological property of slurries, properties of green bodies and sintered bodies were investigated. AN-2000 was selected as the dispersant for obtaining slurries with high solid loading and low viscosity. The solid loading of suspension that can meet the requirement for casting was as high as 52 vol%. However, it was found that the highest relative density of the green body and the sintered body separately reached 66·17% and 85·38% when the solid loading came to 50 vol%, while the flexural strength of them were 13·60 MPa and 62·71 Mpa. Once the solid loading increased to 52 vol%, the relative density and mechanical properties of the green body decreased noticeably, which caused by the increase of the slurry viscosity. Besides, SEM images proved that green bodies and sintered bodies had the homogeneous microstructure when the solid loading was 48-50 vol%. As the solid loading was 52 vol%, hard agglomerations and pores formed in the green body, which had a significant influence on the properties of the sintered body.